2021
DOI: 10.1021/acs.langmuir.1c02488
|View full text |Cite
|
Sign up to set email alerts
|

Impact Dynamics of Nanodroplets on V-Shaped Substrates: Asymmetrical Behavior and Fast-Rebound Dynamics

Abstract: Controlling the drop impact behaviors plays an important role in both designing surface functional materials and improving industrial techniques. Here, the impact dynamics of nanodroplets on “V-shaped” substrates is studied, which is manifested as asymmetrical spreading and retraction behaviors that could be weakened by increasing the angles of the “V” shape, accompanied by the evolution of the shape from leaf-like, stripe-like, to dumbbell-like at v = 20 Å/ps. When v increases to 40 Å/ps, the previously depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Their results showed that when the angle of the inclined surface was small, the droplets formed long tails, while the angle of the inclined surface was large, the droplets had shapes closer to teardrops. For a V-shaped wall (namely inclined walls with confined space), to the best knowledge of the present authors, there are only two publications by Agrawal et al (Agrawal, Khurana, & Dhar, 2021) and Li et al (T. Li & Wu, 2021). Agrawal et al (Agrawal et al, 2021) studied experimentally the collisions of droplets against V-shaped valleys.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Their results showed that when the angle of the inclined surface was small, the droplets formed long tails, while the angle of the inclined surface was large, the droplets had shapes closer to teardrops. For a V-shaped wall (namely inclined walls with confined space), to the best knowledge of the present authors, there are only two publications by Agrawal et al (Agrawal, Khurana, & Dhar, 2021) and Li et al (T. Li & Wu, 2021). Agrawal et al (Agrawal et al, 2021) studied experimentally the collisions of droplets against V-shaped valleys.…”
Section: Introductionmentioning
confidence: 91%
“…However, the effect of eccentricity ratio was not considered in their work. Li et al (T. Li & Wu, 2021) investigated droplets impacting V-shaped substrates using molecular dynamics. In their work, two collisions were observed: rebound and deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an asymmetric V-groove was designed on the superhydrophobic surfaces for achieving more than 700% increase in energy conversion efficiency, which not only effectively enhances the velocity of coalescence-induced droplet jumping, but also randomly changes the jumping direction by controlling the groove angle . Additionally, some experimental studies also reported many well-designed structures that are useful to promote the self-propelled jumping behaviors of the coalesced droplet, such as the nanograss zigzag structures, hierarchical microcone structures, , and V-shaped grooves. , …”
Section: Introductionmentioning
confidence: 99%
“…22 Additionally, some experimental studies also reported many well-designed structures that are useful to promote the self-propelled jumping behaviors of the coalesced droplet, such as the nanograss zigzag structures, 23 hierarchical microcone structures, 24,25 and V-shaped grooves. 26,27 In addition to the surface structures, the droplet itself also plays a critical role in the coalescence-induced jumping behaviors. One concern first raised is the size effect.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Gao et al investigated the phenomenon of droplet impinging on the surface of nanopillars under microscopic conditions and introduced the parameter of solid fraction (representing surface roughness) to modify the maximum spreading factor model. Liu et al and Li et al analyzed the dynamic behavior of nanodroplets impinging on a single ridge and a single-groove structure, respectively. Both structures can significantly reduce the contact time of the droplets.…”
Section: Introductionmentioning
confidence: 99%